Ja, nej eller kanske? - En undersökning av frivillighetsrekvisitet i 6 kap. 1 § Brottsbalken - Augustinsson,Therese (2020)
The purpose of this thesis is to examine the requirement of consent in chapter 6 section 1 of the Swedish Criminal Code (brottsbalken, SFS 1962:700) from a legal security perspective. First by examining how the legislator described the requirement in the legislative history and in the text of the law and thereafter by analyzing court cases where the requirement has been applied. This is to decide if the criticism regarding the unpredictability of the legislation has been justified. The discussion about the requirement of consent began more seriously in 2001 but not until the first of July 2018 the government voted for the so called “law of consent”. In the legislative history a few starting points are given in how the requirement should be used in the assessment of whether there has been a consent or not. However, in the end the legislator delegates to the adjudication to make an assessment in the individual case. The law was met with criticism. Among else, the legislator’s vagueness in the legislative history is one problem that has been highlighted. Finally, the conclusion is that the unpredictability of the requirement of consent is not such a big problem that it is unacceptable. The court cases that are evaluating the new legislation have been comparatively congruous. There are some weaknesses that leads to some unpredictability. In the cases the judges have the hard task to do a normative assessment within an area without any legal standards of what that is a correct behavior. Yet the judges have been consistent and have followed those guidelines they were given in the legislative history. Considering those advantages the new law has meant, like the expanded focus on the sexual self-determination, the unpredictability has not been such a big issue that the law should not have been adopted because of it.
Keywords: Straffrätt; våldtäkt; frivillighet; frivillighetsrekvisit; samtyckeslag